PENGEMBANGAN COMPUTER BASED INSTRUCTIONAL MATERI “HAJI” DI MADRASAH ALIYAH - Setria Utama Rizal; Dadung Maulana; Mazrur Mazrur (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
Hajj is one of the important materials in Islamic religious education whose learning achievements not only include cognitive aspects but also psychomotor and affective aspects. This requires learning media that can facilitate teachers in achieving the achievement. This study aims to develop fiqh learning media on Hajj material. In this study, the product was assessed using the assessment of several questionnaires based on the results of the product trial tested to two experts, namely: media experts and material experts and 10 students. The results of this study found that adobe flash-based media Flash Cs 6 has good quality. This research design uses the development model, the Addie model, this model uses five stages, namely analysis, design, development, implementation, and assessment. The results of the study on the development of learning media based on ADOBE FLASH CS 6 in the Hajj class X Ma Muslimat NU Palangka Raya have been developed. Evidenced by the results of validation by a media expert on the display aspect of obtaining a value of 4.5 and for the aspect of programming to get a value of 4.5 and for validation by the material expert for the learning aspect of obtaining a value of 4.8 and the content aspect gets a value of 4.7. So, this product is biased to be valid. So, from the results of the data obtained, the product in the immunity of the two valid criteria according to the material and media experts.Keywords: Adobe Flash CS6, Learning Media, Hajj, Aliyah Madrasah